Structurally simple synthetic 1, 4-disubstituted piperidines with high selectivity for resistant Plasmodium falciparum - Moses N. Ngemenya; Grace Ntube Abwenzoh; Hermia Nalova Ikome; Denis Zofou; Fidele Ntie-Kang; Simon M. N. Efange (BMC, 2018)
Abstract Background Emergence of resistance to artemisinins and some of their combinations in chemotherapy of clinical malaria has intensified the search for novel safe efficacious antimalarial molecules. Fourteen synthetic 1, 4-disubstituted piperidines with simple molecular structures were evaluated in this study. Methods Antiplasmodial activity were determined against cultured chloroquine-sensitive 3D7 and resistant Dd2 strains of P. falciparum by in vitro parasite growth inhibition. A primary screen was done to identify active compounds by fluorescence microscopy followed by a secondary screen to determine IC50 and IC90 values of active compounds by the parasite lactate dehydrogenase assay. Cytotoxicity of active compounds was assessed using the MTT/formazan assay and selectivity indices (SIs) determined. Optical densities were analysed to obtain experimental results. Results The compounds produced 56 to 93% inhibition of parasite growth at 40 μg/mL. Eight compounds (2 ketone, 5 alcohol and one amine analogues) showed high activity (IC50s between 1 and 5 μg/mL). Nine compounds were highly selective for the parasite (SIs = 15 to 182). Three promising (alcohol) analogues were identified: [1-(4-fluorobenzyl) piperidin-4-yl] [4-fluorophenyl] methanol, (7), [1-(3, 4-dichlorobenzyl) piperidin-4-yl] [4- fluorophenyl] methanol (8) and [1-(4-bromobenzyl) piperidin-4-yl] [4- fluorophenyl] methanol (11) which were more active on the resistant strain (IC50 values between 1.03 to 2.52 μg/mL), than the sensitive strain (IC50 values between 2.51 to 4.43 μg/mL). Conclusions The alcohol analogues were the most active and most selective for the parasite with three promising hit molecules identified among them, suggesting the hydroxyl group at C-7' in these alcohol analogues is contributing greatly to their antiplasmodial activity. Further exploration of the core structure using chemistry approaches and biological screening including in vivo studies in an animal model of malaria may yield important antimalarial leads.